Macrophage inflammatory protein-1β as a novel therapeutic target for renal protection in diabetic kidney disease - Chang, Ting-Ting; Li, Szu-Yuan; Lin, Liang-Yu; Chen, Ching; Chen, Jaw-Wen (Biomedicine & pharmacotherapy, 2023)
Diabetic kidney disease (DKD) is the leading cause of end-stage renal disease worldwide and the prevalence of DKD has increased over recent decades. Inflammation is involved in the development and progression of DKD. In this study, we explored the potential role of macrophage inflammatory protein-1β (MIP-1β) in DKD. Clinical non-diabetic subjects and DKD patients with different levels of urine albumin-to-creatinine ratio (ACR) were enrolled in the study. Leprdb/db mice and MIP-1β knockout mice were also used as mouse models for DKD. We found that serum MIP-1β levels were elevated in the DKD patients, especially those with ACRs that were less than or equal to 300, suggesting that MIP-1β is activated in clinical DKD. The administration of anti-MIP-1β antibodies attenuated DKD severity in the Leprdb/db mice, which also showed reduced glomerular hypertrophy and podocyte injury, as well as decreased inflammation and fibrosis, suggesting that MIP-1β plays a role in the development of DKD. The MIP-1β knockout mice showed improved renal function and decreased renal glomerulosclerosis and fibrosis in DKD. Furthermore, podocytes from the MIP-1β knockout mice showed less high glucose-induced inflammation and fibrosis compared to those from wild-type mice. In conclusion, the inhibition or deletion of MIP-1β protected podocytes, modulated renal inflammation, and ameliorated experimental DKD, suggesting that novel anti-MIP-1β strategies could potentially be used to treat DKD. [Display omitted] •The pathogenesis and therapies of diabetic kidney disease (DKD) have not been fully clarified.•Macrophage inflammatory protein-1β (MIP-1β) is an inflammatory chemokine.•This study shows the potential relevance of MIP-1β in clinical DKD and explores its mechanistic insights.•MIP-1β inhibition can decrease inflammation, protect kidney podocytes, and ameliorate DKD.•This study provides a novel rational for an anti-MIP-1β strategy as a potential therapy for DKD.